Case Report: Enhancing lead extraction techniques: a novel approach using a loop formed by an ablation catheter and a gooseneck snare - Li, Jun; Wang, Lei; Li, Xiaofang; Li, Na; Shao, Xin; Zhang, Anxin; Shu, Yan; Wang, Haixiong (Frontiers in Cardiovascular Medicine, 2024)
Procedure difficulty and complexity increase with the age of the lead to be extracted; regarding the extraction of old (>20 years) leads, procedures are more time-consuming and require advanced tools and a complex technique. In this case, we retrieved a very old (>30 years) lead using a loop formed by a catheter and a gooseneck snare. The catheter was rotated to achieve the removal of the lead-bound sites. Lead was successfully retrieved using a Needle’s Eye Snare.